Sphenoid Mucocele Mimicking an Orbital Apex Syndrome - Izzi, Mohd Zul; Mohamad, Sakinah; Mohamad, Amran; Ramli, Ramiza R; Hussein, Adil (International Journal of Human and Health Sciences (IJHHS), 2022)
Mucoceles are expansile cystic lesions found within the paranasal sinuses lined by pseudostratified epithelium and usually developed due to the obstruction of the sinus ostium. The frontal sinus is most commonly affected followed by ethmoidal sinuses. Meanwhile, the isolated mucocele of the sphenoid sinus alone is rarely reported. Here, we report a case of sudden onset of blurry vision with ophthalmoplegia presented to an ophthalmology clinic, which led to a suspicion of orbital apex syndrome. This case was then referred to the otorhinolaryngology (ORL) team for surveillance assessment. Routine ORL examinations were insignificant, and the rigid nasal endoscopic evaluation showed normal findings. However, the diagnosis of sphenoid mucocele was revealed by the computed tomography of the paranasal sinuses. The mucocele in the sphenoid was drained via endoscopic sphenoidotomy and posterior septectomy gave us an adequate view and room for our procedures. Her visual acuity was immediately improved postoperatively. CT paranasal sinus is important to investigate the cause of orbital apex syndrome. Normal nasal endoscopic findings never rule out the sphenoid mucocele. Isolated sphenoid sinus mucocele is an infrequent entity, however, such diagnosis should be kept in mind by ophthalmologists as well as otorhinolaryngologists in a case of headache, visual disturbance, and external ophthalmoplegia. Early intervention will reverse the pathological manifestation and prevent permanent blindness or neurological deficit. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S25